Hubungan Prenatal Yoga dengan Kecemasan pada Ibu Hamil - Siti Rahmadani; Nurul Lidya; Yunita Laila Astuti; Diana Hartaty Angraini; Jusuf Kristianto (Jurnal Health Sains, 2023)
In pregnancy, anxiety is a common psychological condition. Moreover, when pregnant women enter the third trimester and are approaching the estimated delivery. Pregnancy-related anxiety is also considered to be different from anxiety disorders in general. This due to the specific characteristic of anxiety, in the form of concerns about facing childbirth, the baby's condition, and mother appearance. Pregnancy-related anxiety needs to be identified in order to prevent problems for the mother and baby, such as postpartum depression, delayed fetal development and premature birth. Anxiety in pregnancy can be alleviated with prenatal yoga. Yoga provides favorable benefits for pregnant women, both physically and psychologically, including in reducing anxiety for pregnant women. This study aimed to identify the relationship between prenatal yoga and anxiety in pregnant women. This was a cross-sectional study. The population in this study were all pregnant women at the Depok Regional Health Center. This research was conducted in June-October 2022. The sample size was taken by purposive sampling. Data collection in this study used the HARS anxiety scale to measure the level of anxiety in pregnant women. Data analysis using Chi-Square test, multivariate analysis using Logistic Regression. Chi-Square test value shows that there was a relationship between prenatal yoga and anxiety in pregnant women (p value = 0.046). The results of multivariate analysis showed that only occupational factors that affected anxiety in pregnant women with p value = 0.010 (p < 0.005). There was a relationship between prenatal yoga and anxiety in pregnant women so that it provides recommendations to facilitate prenatal yoga for pregnant women in order to carry out pregnancy comfortably.